THE DEVELOPMENT OF SELECTIVE AND UNSELECTIVE FISHING GEAR OWNED BY FISHERMAN AT THE NORTH COAST OF CENTRAL JAVA - Asriyanto .; Agung Setiarto (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Introduction : The Utilization of fisheries resource in Indonesia waters has just achieved about half (56.06%) of the maximum sustainable yield. In the north coast of Central Java, which has a coastal line of about 450 kilometers, 20 types of fishing gear are owned by fishermen. Experiment : Data were collected from Annual Report 1993 – 1997 issued by Central Java Fisheries Agency. Twenty types of fishing gear were classified into 6 groups, i.e. seine nets, purse seine, gillnets and trammel nets, lift nets, lines, and traps. Two of them were categorized as unselective fishing gear, i.e. seine nets and purse seine, whereas the other 4 were classified as selective ones. The number of each group was expressed in means and percentages and the development/changes thereof was presented in percentage. Results and discussion : The number of unselective fishing gears grew rapidly from 1996 to 1997, i.e. seine nets 17.31% and purse seine 12.07%. on the country the number of selective fishing gear increased slightly or even decreased, for example traps (5.98%), line (4.13%), liftnets (-3.21%), and gill nets & trammel nets (-2.45%). The management of fisheries resources should be focused on the enhancement in the number of selective fishing gear and the extension of their fishing ground, combined with close monitoring on the mesh size of unselective fishing gear.